(untitled) (Kronika Bydgoska, 2013)
The heritage of the Polish People’s Republic is increasingly often in the circle of interests of architecture historians. Undoubtedly, this type research is worth conducting also in case of Bydgoszcz - at that time a very important city experiencing a period o f its dynamic development. This article is an attempt at presenting the entire range o f issues connected with Bydgoszcz architecture and urban planning in the years 1945-1956. The first post-war years were a period of reconstruction conducted under the motto of celebrating the 600th anniversary of the existence of Bydgoszcz and preparations for the Pomeranian Exhibition of Craft, Industry and Trade. At that time, the unfortunate decision to dismantle the Municipal Theatre was made, due to urban planning reasons - the need to make a green square and to order the city centre area. At the same time, erection of the new theatre building to a design by architect Alfons Licznerski was started in another place. An important achievement was the successful commencement of the construction of the Pomeranian Philharmonic edifice and two new housing estates - Leśne and Kapuściska. Infill constructions were added to the buildings in the city centre. In the described period, the dominant architecture was the one constructed with the use o f traditional technology, with simplified forms referring to classical architecture, and within the trend of simple socialist realism. At the same time, in 1950, the works on the spatial development plan for Bydgoszcz were started, indicating the need for extension of the city’s eastern part and for relocation of the city centre.